2013
DOI: 10.1159/000354484
|View full text |Cite
|
Sign up to set email alerts
|

Panax NotoginsengSaponins Promote Endothelial Progenitor Cell Mobilization and Attenuate Atherosclerotic Lesions in Apolipoprotein E Knockout Mice

Abstract: Background: Endothelial progenitor cells (EPCs) derived from the bone marrow (BM) play a key role in the homeostasis of vascular repair by enhanced reendothelialization. Panax notoginseng saponins (PNS), a highly valued traditional Chinese medicine, has been shown to reduce morbidity and mortality from coronary artery disease. The present research was designed to explore the contribution of progenitor cells to the progression of atherosclerotic plaques and the possible modulatory role of PNS in this process. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 41 publications
0
16
0
Order By: Relevance
“…The results of western blot analysis showed that knockdown of [22], and reduced levels of circulating EPCs are predictive of atherosclerotic disease progression and cardiovascular events [23,24]. EPC transplantation has been investigated for the treatment of cardiovascular diseases.…”
Section: Ilk Regulates Akt/gsk-3β Phosphorylation and The Expression mentioning
confidence: 99%
“…The results of western blot analysis showed that knockdown of [22], and reduced levels of circulating EPCs are predictive of atherosclerotic disease progression and cardiovascular events [23,24]. EPC transplantation has been investigated for the treatment of cardiovascular diseases.…”
Section: Ilk Regulates Akt/gsk-3β Phosphorylation and The Expression mentioning
confidence: 99%
“…Previous studies has been reported that PNS could stimulate alkaline phosphatase activities and increase the number of osteoblasts in vitro, promote the proliferation of bone marrow mesenchymal stromal cells [8], and is effective in promoting blood circulation to remove stasis [9]. Recent studies suggest that PNS may be a potential therapeutic methods for treating bone nonunion, osteoporosis and osteonecrosis [10].…”
Section: Introductionmentioning
confidence: 99%
“…A higher PNS dose (100 mg/kg) than that used in the current study, administered once through the caudal vein, was reported to decrease blood pressure in SHR after 20 min . Numerous prior studies have indicated that 30–120 mg/kg of PNS is optimal for protection against cerebral ischaemia in animal models . In the present study, the lowest dose was therefore selected, 30 mg/kg of PNS, which is six times the clinical dose (5 mg/kg).…”
Section: Discussionmentioning
confidence: 89%
“…5 Numerous prior studies have indicated that 30-120 mg/kg of PNS is optimal for protection against cerebral ischaemia in animal models. 6,29,30 In the present study, the lowest dose was therefore selected, 30 mg/ kg of PNS, which is six times the clinical dose (5 mg/kg). As expected, long-term administration of PNS to SHRSP.ZF rats reduced blood pressure by 15%.…”
Section: Discussionmentioning
confidence: 99%